Ethylene Acts as a Negative Regulator of the Stem-Bending Mechanism of Different Cut Snapdragon Cultivars - Naing, Aung Htay; Soe, May Thu; Yeum, Jeong Hyun; Kim, Chang Kil (Frontiers in Plant Science, 2021)
This study investigated whether ethylene is involved in the stem bending mechanism of three different snapdragon cultivars ‘Asrit Red,’ ‘Asrit Yellow,’ and ‘Merryred Pink,’ by treating their cut stems with an ethylene-releasing compound (ethephon), an ethylene-synthesis inhibitor [silver thiosulfate (STS)], and distilled water (as the control). Ethephon completely prevented stem bending in all cultivars, whereas STS exhibited a higher bending rate compared with the control. The bending rates were influenced by several factors, such as the degree of stem curvature, relative shoot elongation (RSE), ethylene production, and lignin content, indicating their involvement in the stem bending mechanism of the cultivars. The analysis of the expression of genes involved in the ethylene and lignin biosynthetic pathways also supported the importance of lignin and ethylene in the stem bending mechanism. Taken together, as ethephon completely prevented stem bending of the three snapdragon cultivars, this study suggested that ethylene acts as a negative regulator of the stem bending mechanism of snapdragon cultivars, and the information will be valuable for the prevention of stem bending in other commercially important ornamental flowers